Estimation of Survival of American Eels After Passage Through a Turbine at the St. Lawrence-FDR Power Project, New York (DRAFT Final Report) - Normandeau Associates Inc; Skalski, J R (ScholarWorks@UMass Amherst, 1998)
None supplied